Legal Ambiguity Pengecualian Pembayaran Upah Minimum Bagi Pengusaha Mikro dan Kecil Pasca UU No. 6 Tahun 2023 tentang Cipta Kerja - Muklis Al'Anam; Armadani Armadani (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
The norms contained in a rule reflect the morals of the rule or lead to the morals of the legislator. The problem of wages for workers/labourers has become a hot legal issue to be criticised and discussed, since the issuance of Government Regulation Number 51 of 2023 as part of the revision of Government Regulation Number 36 of 2021 concerning Wages. Minimum wage and living wage provisions are an important part of the labour aspect, which is an absolute right for workers/labourers. Article 36 of the regulation regulates wage exemptions for micro and small entrepreneurs, where micro and small entrepreneurs in Government Regulation No. 7 of 2021 are listed as having capital and output of up to billions. In ratio legis, it is impossible to say that micro and small businesses with capital and sales up to billions of rupiah. So that the legal research used is a normative method, which studies the norms in the rules discussed based on the statutory approach and conceptual approach as the basis for thinking in this article. Therefore, this research provides legal solutions related to the issues discussed concerning minimum wage eligibility without any exceptions.